Dual identity in context: The role of minority peers and school discrimination. (11th December 2021) - Kende, Judit; Baysu, Gülseli; Phalet, Karen; Fleischmann, Fenella
Abstract: Immigrant‐origin minority adolescents combine their common national identity with distinct ethnic identities. Depending on different social ecologies they develop more or less compatible dual identifications. Taking an ecological approach to ethnic‐racial socialization (ERS), we investigate how schools and peers as socializing agents can afford compatible ethnic and national identifications. We draw on the Children of Immigrants Longitudinal Survey of 944 Turkish and Moroccan minority adolescents in 229 classrooms across 55 Belgian secondary schools with low (10%) to high minority presence (60%+). On average ethnic and national identifications were not significantly associated. In support of the protective role of minority peers, multilevel modeling revealed that national and ethnic identifications were more compatible in classrooms with more minority peers; while school discrimination undermined compatibility only in classrooms with fewer minority peers. We conclude that minority peers are key agents in the socialization of compatible ethnic and national identities.